Taenia solium cysticercosis in India: A vetero-medical update - Pathak, K M L; Chhabra, M B (The Indian Journal of Animal Sciences, 2012)
Cysticercosis is an infection caused in pigs and man by the metacestode of Taenia solium, the pork tapeworm of man. It is a major food-borne zoonosis, which is an economic constraint to the pig industry as well as a serious medical problem. Neurocysticercosis (NCC) is regarded as the most frequent parasitosis of the central nervous system (CNS) and the most common cause of epilepsy in India. The commonest lesions are presented as granuloma. Unhealthy pig- rearing practices, lack of sanitation, inadequate meat inspection, rural-to-urban migration and other factors have contributed to the endemic status of the disease in India. At the same time, increasing number of detections consequent to improved serological and imaging techniques have aided definitive diagnosis, increasingly incriminating NCC as the cause of considerable morbidity and mortality with resultant socio-economic burden. While there are sporadic reports on pigs, largely based on prevalence at postmortem or serological, considerable epidemiological, diagnostic and clinical data has come up on human side in recent years. In the spectra of clinical manifestations, ocular disease and disseminated cysticercosis are being reported with increasing frequency. Detection and anthelmintic treatment of human taeniasis is the main component of a control strategy. Porcine cysticercosis should also receive due attention, and development of an onchosphere antigen-based vaccine is a promising line. The problem calls for improved collaboration between medical and veterinary services, community involvement and greater awareness of public health workers.